Integrating ethnomathematics into a transformation geometry module to enhance self-efficacy - Bela, Maria Editha; Wewe, Melkior (Al-Jabar: Jurnal Pendidikan Matematika, 2024)
Background: Improving self-efficacy is essential for student success in mathematics, especially in complex topics like transformation geometry. Incorporating ethnomathematics into instructional modules provides a meaningful connection between mathematical concepts and cultural contexts, which can enhance student engagement and confidence.Aim: This research focuses on developing a teaching module grounded in ethnomathematics to foster self-efficacy among Class XI high school students in transformation geometry. The study also evaluates the module's validity and practicality.Method: Using the ADDIE framework (Analyze, Design, Develop, Implement, Evaluate) within a Research and Development (R&D) approach, the study utilized expert validation sheets to assess content and design quality. Practicality was measured through teacher and student feedback collected via questionnaires. Data were analyzed through qualitative and quantitative descriptive methods.Results: Expert reviews on content and design yielded an average score of 86, indicating the module's strong validity. Feedback from teachers and students produced an average score of 85.72, demonstrating the module's high level of practicality.Conclusion: The ethnomathematics-based module is validated as both effective and practical, making it a valuable resource for improving self-efficacy in transformation geometry.